2019
DOI: 10.1371/journal.pone.0218524
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between Toxoplasma gondii infection and depression? A systematic review and meta-analysis

Abstract: Background Toxoplasma gondii ( T . gondii ) is an obligate intracellular opportunistic parasite that is the causative agent of toxoplasmosis. This parasite accounts for mental disorders; however, the relationship between T . gondii infection and depressive disorder is unclear. Regarding this, the present systematic review and meta-analysis was conducted to investigate the scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 60 publications
3
17
2
1
Order By: Relevance
“…This review describes the main results of studies that evaluated the association between ET and major psychiatric disorders (schizophrenia, BD and MDD), using the criteria and diagnostic interviews summarized in the DSM-IV and later manuals. While there is consensus regarding the lack of association between ET and MDD, 48 there are conflicting findings regarding its association with schizophrenia and BD, since we observed heterogeneity of results. A plausible explanation is the above-mentioned strain hypothesis, 12 , 14 , 32 since different regional strains of T. gondii affect different populations and could mediate different neuropsychiatric effects.…”
Section: Discussioncontrasting
confidence: 67%
“…This review describes the main results of studies that evaluated the association between ET and major psychiatric disorders (schizophrenia, BD and MDD), using the criteria and diagnostic interviews summarized in the DSM-IV and later manuals. While there is consensus regarding the lack of association between ET and MDD, 48 there are conflicting findings regarding its association with schizophrenia and BD, since we observed heterogeneity of results. A plausible explanation is the above-mentioned strain hypothesis, 12 , 14 , 32 since different regional strains of T. gondii affect different populations and could mediate different neuropsychiatric effects.…”
Section: Discussioncontrasting
confidence: 67%
“…The front-line medical staff will not only bear the work pressure of overload, but also face the huge risk of infection (2). Stress represents the main environmental risk factor for psychiatric illnesses, and in a long-term stress state, people can be more prone to depression or other mental disease (3), which will also increase the risk of infection (4)(5)(6). Therefore, it is necessary to investigate the psychological state of the first-line anti-epidemic medical staff and give them necessary psychological interventions if they have anxiety or depression.…”
Section: Introductionmentioning
confidence: 99%
“…A community-based study found that T. gondii seropositivity was associated with anxiety, but not depression (Markovitz et al ., 2015), and a cohort study indicated that toxoplasmosis was associated with anxiety (Flegr and Horáček, 2020). Two meta-analyses concluded that T. gondii infection was not associated with depression (Wang et al ., 2014; Nayeri Chegeni et al ., 2019). Notably, a Danish study found that T. gondii seropositivity was associated with moderate–severe depression, but not mild–severe (Bay-Richter et al ., 2019 a ; Nayeri Chegeni et al ., 2019); therefore, severity of depression may be one possible reason for conflicting relationships between T. gondii infection and depression reported in the literature.…”
Section: Discussionmentioning
confidence: 99%